Change management in e-learning implementation in Malaysian private Higher Education Institutions / Sheiladevi Sukumaran - Sheiladevi , Sukumaran (2016)

(untitled)
The purpose of this research were to analyses the status and trend, to explore the problems and challenges, to explore the ways to facilitate educators and to analyses the impact of certain identified variables to adapt change management due to e-learning implementation in Malaysia private higher education institutions focusing on educators’ perspectives. The conceptual framework model was modified in combination of various theoretical framework of Systemic Change Model which were by Joseph (2010) and Laird (2004) E-learning Cycle Model. Self-administered questionnaire was the data collection instrument for quantitative method and interviews were conducted as data collection method for qualitative research. The samples were educators from private higher education institutions with vision or mission based on e-learning implementation in Malaysia. The questionnaire was adapted from Siebel 4.0-2 Survey Questionnaires (SSQ) by Hambling, 2010.As per findings, through review of the vision and mission in the selected private higher education institutions they integrated teaching and learning, advancement of the knowledge based on e-learning and leadership in service and outreach. The study also found that majority of educators’ in the respective institutions was Chinese female lecturers with 2-5 years of working experience. Majority of the lecturers were not married and in between 25-35 years old. Majority of the lecturers were Master’s Degree holder and full time working in the respective institutions. This revealed that the junior lecturers were comparatively better in various perspectives such as in different software programs usage, exploring websites and consumption of multimedia tools for e-learning purposes than the senior lecturers in the respective private higher education institutions.There were 99% of the respondents stated that there were no policy on e-learning at respondents’ institutions. Majority of the respondents also strongly agreed that more experts were needed to handle change management due to e-learning implementation. It also revealed that advancement in internet with digital realm were reshaping the dimension of e-learning implementation. According to these research findings, as progress through the processes of change management the management facing challenges when creating a new change management plan, engaging with stakeholders, countering resistance to change, and measuring the effectiveness of implemented changes to meet the strategic goals. This study also revealed that 5 availability of skilled trained staff and educators' working relationship with e-learning centers in each institution was vital for overall success of change management in elearning implementation among educators in private higher education institutions. The study found that educators' lack of innovation, ineffective roles in decision making for e-learning implementation acquisition were the reason for their resistance to change, fear of change and feeling of insecurity. The study found that a quality and standard in handling change management due to e-learning would enhance e-learning utilization among educators' in private higher education institutions in Malaysia. As a concluding remark, the successful change management among educators needs the concerted efforts of all stakeholders.